Prevalence of endometriosis in diagnostic and therapeutic laparoscopy among women with chronic pelvic pain - Siivonen, Saima; Suvitie, Pia A (SAGE Publications, 2026)
Introduction:
When peritoneal endometriosis is clinically suspected, diagnostic and therapeutic laparoscopy may be offered after failed or unsuitable medical therapy. Our objective was to determine how often endometriosis is verified in these laparoscopies.
Methods:
In our registry-based historical cohort we identified 296 women aged 15–49 years undergoing laparoscopy due to chronic pelvic pain, between 2009 and 2020 at Turku University Hospital. Women without preoperative ultrasound findings and no history of endometriosis were included in the study.
Results:
Macroscopic endometriosis was detected in 52.4% of laparoscopies, and the rate was similar throughout the study period. Peritoneal endometriosis was found in 52% of participants, deep endometriosis in 4.7%, and a small endometrioma in 2%. Women with and without endometriosis reported similar preoperative rates of acyclic abdominal pain (91.8% vs 93.9%, p = 0.64) and dyspareunia (84.6% vs 78.9%, p = 0.32), while dyschezia was significantly more common among women with endometriosis (44.4% vs 26.9%, p = 0.006). The prevalence of dysmenorrhea is not reported, as 62.5% of patients used hormonal therapy commonly aiming to amenorrhea. The median age at the onset of symptoms was significantly lower in women with endometriosis (14 vs 19, p = 0.048).
Conclusions:
Endometriosis was confirmed in 52.4% of the women undergoing laparoscopy due to chronic pelvic pain, and in most women, peritoneal endometriosis was the only finding. However, the other half of the women did not have endometriosis despite having similar pain symptoms. It remains unknown whether patients benefit long-term from undergoing diagnostic and therapeutic laparoscopy.